(untitled) (American Journal of Islam and Society, 2003)
Through the lens of genre, Heck examines Kitab al-Kharaj wa Sina ’at a/Kitabah ("The Book of the Land-Tax and the Craft of Writing/ Secretaryship"), a work on Islamic administration composed in Baghdad in the early fourth/tenth century by the prominent secretary Qudamah ibn Ja’far (d. 337/948). His analysis ofQudamah’s manual, which belongs to a body of texts that emerged in the late third/ninth century and focused primarily on the concerns of state officials, proceeds by breaking it into constituent parts and considering each one individually in relation to earlier and contemporary works in related genres. The result is a detailed appreciation for the work’s characteristics and relative merits; showing how one author constructed human knowledge; how he articulated the relationship between knowledge, religion, and the ’Abbasid state; and how this por trayal differed from other contemporary schemes. The organization of the original work was as follows: I. Introduction, 2. The Art of Writing, 3. Language and Rhetoric, 4. Bureaus of the Imperial Administration, 5. Bureaus of the Imperial Administration, 6. Geography, 7. Fiscal Law, and 8. Political Thought. Unfortunately, only chapters 5-8 survive. The unique manuscript at Istanbul’s Koprulu Library was published in facsimile edition in 1968 and edited in 1981 (the 1981 edition, Heck reports, contains numerous errors). The author’s discussion uses the rubrics of language in chapter 2 (parts 2-5), geography in chapter ...